Comunicación literaria: análisis del discurso en la novela de George Orwell: La rebelión en la granja, y los aspectos semióticos de la novela” - López Taza, Renata Anai (2024)
ABSTRACT: The main purpose of this research study was to analyze the characters in George Orwell's novel " Rebelión en la granja" from a semiotic perspective, as well as to understand their actions from the theory of power, and how they represented a political structure in Russia, as well as the satire that the author made by using animals to represent the politicians of the situation that the country was going through. The objective was to analyze the discourse of Orwell's novel "Animal Farm" and the semiotic aspects that affect it, this could be achieved through the methodology that was part of the research process, which consisted of a matrix of discourse analysis, which allowed to demonstrate the sense of power behind each speech of leading characters in the work, and likewise, a matrix of semiotic analysis that was based on Peirce's triad, which has as elements: sign, object, representation. The research process carried out allowed us to determine that Orwell's novel talks about a political ideal, and also, how he proposes this ideal when those in power do not manage to leave ambition aside to ensure the struggle and equality of the people. Orwell's novel clearly becomes a satire on Stalinism in Russia, and also a way of judging socialism when power is the true ideal of those who are at the helm of societies.